A characterization of operator order via grand Furuta. Issue 5 (2001) - seo, Yuki
Abstract : As an application of the grand Furuta inequality, we shall show a characterization of usual order associated with operator equation and a Kantorovich type order preserving operator inequality by using essentially the same idea of [9].